Heat source free water floating carbon nanotube thermoelectric generators - Tomoyuki Chiba (Nature Portfolio, 2021)
Abstract Thermoelectric generators (TEGs) produce electric power from environmental heat energy and are expected to play a key role in powering the Internet of things. However, they require a heat source to create a stable and irreversible temperature gradient. Overcoming these restrictions will allow the use of TEGs to proliferate. Therefore, we propose heat source-free water-floating carbon nanotube (CNT) TEGs. Output voltage and power are generated by the temperature gradient in the CNT films in which water pumping via capillary action leads to evaporation-induced cooling in selected areas. Furthermore, the output voltage and power increase when the films are exposed to sunlight and wind flow. These water-floating CNT TEGs demonstrate a pathway for developing wireless monitoring systems for water environments.